Fine tuning of the catalytic activity of colicin E7 nuclease domain by systematic N‐terminal mutations. (17th June 2014) - Németh, Eszter; Körtvélyesi, Tamás; Thulstrup, Peter W.; Christensen, Hans E. M.; Kožíšek, Milan; Nagata, Kyosuke; Czene, Anikó; Gyurcsik, Béla
Abstract: The nuclease domain of colicin E7 (NColE7) promotes the nonspecific cleavage of nucleic acids at its C‐terminal HNH motif. Interestingly, the deletion of four N‐terminal residues (446–449 NColE7 = KRNK) resulted in complete loss of the enzyme activity. R447A mutation was reported to decrease the nuclease activity, but a detailed analysis of the role of the highly positive and flexible N‐terminus is still missing. Here, we present the study of four mutants, with a decreased activity in the following order: NColE7  >> KGNK > KGNG ∼ GGNK > GGNG. At the same time, the folding, the metal‐ion, and the DNA‐binding affinity were unaffected by the mutations as revealed by linear and circular dichroism spectroscopy, isothermal calorimetric titrations, and gel mobility shift experiments. Semiempirical quantum chemical calculations and molecular dynamics simulations revealed that K446, K449, and/or the N‐terminal amino group are able to approach the active centre in the absence of the other positively charged residues. The results suggested a complex role of the N‐terminus in the catalytic process that could be exploited in the design of a controlled nuclease.